Carbon capture technologies for climate change mitigation: A bibliometric analysis of the scientific discourse during 1998-2018 - Osaze Omoregbe; Abdullah Naseer Mustapha; Robert Steinberger-Wilckens; Ahmad El-Kharouf; Helen Onyeaka (Energy Reports, 2020)
There are four strategies to combating global warming, namely by directly reducing greenhouse gas emissions, or indirectly through expanding renewable energy employment, more efficient use of energy, or a wide range of climate policies. This study reports a bibliometric analysis of direct carbon dioxide emission reduction through carbon capture. The research trend in carbon capture within the three main types of technologies, namely pre-combustion, post-combustion and oxy-fuel combustion, was investigated using publications from 1998 to 2018 retrieved from the Web of Science database. It was found that from 1998-2007 there was little or no research output on carbon capture, until 2008, when legislation on climate change abatement was introduced and public and industry awareness of clean fossil energy options grew. With these motivating factors, 55 countries engaged in carbon capture technologies and related research in which the United States has the most research output followed by the UK and, China. Among the carbon capture technologies commonly studied, the bibliometric analysis based on a network map showed that post-combustion capture is the most referenced carbon capture technology with about 80.9% of total publications retrieved. oxy-fuel combustion had the lowest number of publications (3.4%).
Keywords: 330; Bibliometric analysis; Carbon capture; Oxy-fuel combustion; Post-combustion capture; Pre-combustion carbon capture